Artificial general intelligence 4th International Conference, AGI 2011, Mountain View, CA, USA, August 3-6, 2011. Proceedings - Schmidhuber, Jürgen; Thórisson, Kristinn R.; Looks, Moshe (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Artificial General Intelligence, AGI 2011, held in Mountain View, CA, USA, in August 2011. The 28 revised full papers and 26 short papers were carefully reviewed and selected from 103 submissions. The papers are written by leading academic and industry researchers involved in scientific and engineering work and focus on the creation of AI systems possessing general intelligence at the human level and beyon
Electronic reproduction.
Keywords: Computer science; Computer software; Information systems; Artificial intelligence; Artificial intelligence -- Congresses